The Green New Deal in the Global South: An Analysis of the Potential for Sustainable Environment in China, Pakistan, and India - Rahman, Zia Ur; Ullah, Saeed; Khan, Wajid; Kamran, Muhammad; Awan, Tahira; Ullah, Ikram; Batool, Hafsah (Journal of Environmental Accounting and Management, 2026)
Large-scale industrialization, population growth, and economic development have led to rising energy consumption and environmental degradation, consistently threatening environmental sustainability. This study examines the effects of natural resource consumption, environmental regulations, energy efficiency and conservation, sustainable economic development, institutional quality, and geopolitical risk on environmental quality. A panel dataset covering China, Pakistan, and India (representing the Global South) from 1990 to 2021 was compiled using data from the World Development Indicators, Global Footprint Network, and World Governance Indicators. To analyze the determinants of environmental quality, the study employs advanced econometric techniques, including Bootstrap OLS, Quantile Regression, and the Dynamic Simulated Autoregressive Distributed Lagged model (DS-ARDL). The results reveal that natural resource consumption significantly deteriorates the environmental quality, reducing it by 0.049%. In contrast, environmental regulations, energy efficiency and conservation, sustainable economic development, and institutional quality improve environmental quality by 0.107%, 0.196%, 0.585%, and 1.450% respectively. Moreover, environmental regulation, energy efficiency and conservation, and strong institutions not only enhance environmental quality but also reduce greenhouse gas emissions, thereby supporting sustainable economic development. The analysis also highlights that interaction effects amplify the impact of some variables on environmental quality. The study underscores the critical role of policy interventions in improving environmental outcomes, and relevant policy implications are discussed.